A comparative evaluation of antibiotic and synbiotic supplementation on production performance and necrotic enteritis severity in broilers during an experimental necrotic enteritis challenge - Shah, Bikas Raj; Al Hakeem, Walid Ghazi; Shanmugasundaram, Revathi; Selvaraj, Ramesh K. (Frontiers in Physiology, 2025)
The ban on antibiotics in the poultry diet resulted in re-emergence of several infectious diseases including necrotic enteritis (NE). These infectious diseases are leading to poor health and welfare as well as production and economic loss. Synbiotic could be a potential candidate to replace the antibiotics in poultry diet. Therefore, a 35-day study was conducted to compare the efficacy of synbiotic (PoultryStar®ME) and antibiotic (Stafac®50, Virginiamycin) supplementation during an experimentally induced necrotic enteritis infection. A total of 360 day-old chicks were randomly assigned to four treatment groups: Antibiotic, Challenge + Antibiotic, Synbiotic, and Challenge + Synbiotic, each with 6 replicates. The treatment groups referred as “Challenge + Antibiotic” and “Challenge + Synbiotic” were challenged, while their respective non-challenged treatment groups were “antibiotic” and “synbiotic”. NE in birds was induced by gavaging 1 × 104 oocysts of Eimeria maxima on day 14 (D14) and 1 × 108 CFU/mL of Clostridium perfringens on D19, 20, and 21. Both synbiotic and antibiotic supplementation during the NE challenge did not improve BW gain, feed intake, and feed conversion ratio at the end of the experiment (D0-35). However, antibiotic supplementation reduced mortality during the week of the challenge (D14-21) (P < 0.001). At D21, both synbiotic and antibiotic supplementation during the NE challenge did not decrease the intestinal lesion score (P < 0.001) compared to their respective non-challenged treatment groups. At D21, synbiotic supplementation during the NE challenge did not decrease intestinal permeability (P = 0.04) compared to the synbiotic group. At D21, antibiotic supplementation during the NE challenge increased the CD4+:CD8+ T cells (P < 0.001) in the cecal tonsil. It can be concluded that synbiotic supplementation elicited an immune response, decreasing the inflammatory response in the intestine and ameliorating the NE infection. Therefore, synbiotic could be a potential alternative to replace antibiotics in the poultry industry, but their efficacy needs to be improved through blending additional probiotics and prebiotics, and further exploration is required.